Comparative evaluation of nutritional quality and flavor characteristics for Micropterus salmoides muscle in different aquaculture systems - Zhengxi Wang; Jishu Zheng; Decheng Pu; Peiyuan Li; Xiuli Wei; Dongsheng Li; Lihong Gao; Xuliang Zhai; Changhua Zhao; Yidan Du (Food Chemistry: X)
To investigate the nutritional quality and flavor characteristics of Micropterus salmoides muscle cultivated in the pond (P), in-pond raceway (IPRS), and industrial aquaponics (ARAS) systems, we comprehensively analyzed texture properties, nutrient compositions, and volatile compounds. Our results revealed firmer flesh in P-cultured fish due to greater hardness and mastication. ARAS fish exhibited lower crude fat but higher crude protein and muscle glycogen. Notably, recirculating aquaculture significantly elevated total amino acids, minerals, and ΣPUFA/ΣSFA ratio, enhancing nutritional value. Pyrazine,2-methoxy-3-(2-methylpropyl)-, and β-Ionone were identified as key flavor compounds. Volatile metabolites in all systems were dominated by woody, herbal, and sweet aroma profiles, with ARAS achieving the highest odor activity value, suggesting improved overall flavor. This study underscores the pivotal role of recirculating aquaculture in enhancing Micropterus salmoides quality, positioning it as a new quality productive force.